2011
DOI: 10.1093/toxsci/kfr332
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity Evaluation of Oxidized Single-Walled Carbon Nanotubes and Graphene Oxide on Human Hepatoma HepG2 cells: An iTRAQ-Coupled 2D LC-MS/MS Proteome Analysis

Abstract: Because of their attractive chemical and physical properties, graphitic nanomaterials and their derivatives have gained tremendous interest for applications in electronics, materials, and biomedical areas. However, few detailed studies have been performed to evaluate the potential cytotoxicity of these nanomaterials on living systems at the molecular level. In the present study, our group exploited the isobaric tagged relative and absolute quantification (iTRAQ)-coupled two-dimensional liquid chromatography-ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
79
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(90 citation statements)
references
References 41 publications
6
79
2
3
Order By: Relevance
“…81 Consistent with our results, previous studies also reported that GO can enter the cells by interacting with the plasma membrane and probably temporarily disrupting the phospholipid bilayer or causing plasma membrane invagination in HepG2 cells and neuroblastoma cell lines, including SK-N-BE(2) and SH-SY5Y. 30,112 Mari et al 30 further demonstrated that GO nanoribbons at low concentrations and within 72 h of exposure induced autophagy in neuroblastoma cell lines. Evidence from the presence of cytoplasmic vacuoles, especially in treated SK-N-BE(2) cells, and the induction of the lysosomal proteins LC3 and beclin, which are markers of autophagy, also confirmed that the autophagy is mainly due to ROS induced by GO.…”
supporting
confidence: 90%
“…81 Consistent with our results, previous studies also reported that GO can enter the cells by interacting with the plasma membrane and probably temporarily disrupting the phospholipid bilayer or causing plasma membrane invagination in HepG2 cells and neuroblastoma cell lines, including SK-N-BE(2) and SH-SY5Y. 30,112 Mari et al 30 further demonstrated that GO nanoribbons at low concentrations and within 72 h of exposure induced autophagy in neuroblastoma cell lines. Evidence from the presence of cytoplasmic vacuoles, especially in treated SK-N-BE(2) cells, and the induction of the lysosomal proteins LC3 and beclin, which are markers of autophagy, also confirmed that the autophagy is mainly due to ROS induced by GO.…”
supporting
confidence: 90%
“…25 Oxidative stress and generation of ROS can be involved in the toxic effects of graphene-based nanomaterials. 26 Assessment of ROS production showed a toxic influence of HNC on glioma cells. The interactions of the HNC particles with the U87 cells can lead to excessive ROS generation.…”
Section: Discussionmentioning
confidence: 99%
“…The liver cells were blocked in G2 phase by SWNHs, and the gap between DNA synthesis and mitosis was delayed by the quantity of SWNHs40 in HepG2, which may result from the apoptosis of HepG2 cells. 27 The cell cycle of liver cell lines was associated with the suppression of their proliferation induced by SWNHs.…”
Section: Swnhs Affected Liver Cell Cyclementioning
confidence: 99%
“…34 Mitochondria, as the major source of reactive oxygen species (ROS) and redox machinery in cells, could activate inflammatory cytokines. 32 Oxidative stress had been found in HepG2 cells treated with unmodified or oxidized SWNTs and MWNTs, [25][26][27][28] L02 cells treated with unmodified, carboxyl-modified, or hydroxyl-modified MWNTs, 29 and rat hepatocytes treated with fullerenes C 60 , C 60 (OH) 12 , and C 60 (OH) 24 . 31 Gao et al 19 found that modified MWNTs internalized in lysosomes of human macrophages (THP-1 cells), generated ROS, and lowered mitochondrial membrane potential.…”
mentioning
confidence: 99%